A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages VI ADMINISTRATION Central Organisation The main lines on which the Government propose that the new National Health Service shall be organised will have become clear from the arrangements already described for the various parts of the service. But the form of organisation contemplated may be easier to understand if it is summarised here as a whole. Moreover, there are important proposals affecting the administration of the new service which have not yet been mentioned. It is proposed that central responsibility for the National Service shall rest on the two Health Ministers. Indeed, no other arrangement is possible, having regard to the magnitude of the scheme and the large sums of public money that will be involved. While the service will thus be under general Ministerial control, only one part of it (the new general practitioner service) will be in the main centrally administered, and for most parts of the new service the principle already adopted in the majority of the health services in the past — the principle of local responsibility, with co-ordination at the centre — will be similarly adopted in the future. In the general practitioner service, however, much of the day-to-day administration will be carried out, under the general directions of the Health Ministers, by the two Central Medical Boards already described. Central Health Services Council Although it is on the Health Ministers that responsibility to Parliament for the new Health Service must rest, the Government attach great importance to ensuring that the service is shaped and operated in close association with professional and expert opinion. The provision of a health service involves technical issues of the highest importance, and in its administration, both centrally and locally, the guidance of the expert must be available and must not go unheeded. Otherwise the quality of the service is bound to suffer. The Government propose, therefore, that there shall be set up by statute at the side of the Minister a special professional and expert body, to be called the Central Health Services Council. Its function will be to express the expert view on technical aspects of the Health Service. The Council will differ from the Central Medical Board in that it will be a consultative and advisory body, and not — as the Board will be — an executive body responsible under the Minister's direction for a defined part of the administration of the new Service. The Council will be entitled to advise, not only on matters referred to it by the Minister, but on any matters within its province on which it thinks it right to express an expert opinion. A duty will be placed on the Minister — apart from any other publication of the Council's advice or views which he may make from time to time — to submit annually to Parliament a report on the Council's work during the year. 21 36/H24/41